2020
DOI: 10.1053/j.jvca.2020.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Prospective Study Evaluating Single-Injection Paravertebral Block, Paravertebral Catheter, and Thoracic Epidural Catheter for Postoperative Regional Analgesia After Video-Assisted Thoracoscopic Surgery

Abstract: Objective: Video-assisted thoracoscopic surgery (VATS) has improved patient outcomes; however, postoperative pain remains potentially severe. The objective of this study was to compare adjunct analgesic modalities for VATS, including paravertebral nerve blockade (PVB) and thoracic epidural anesthesia (TEA). Design: Prospective, randomized trial. Setting: Large academic hospital, single institution. Participants: Adult patients undergoing VATS. Interventions: Ultrasound-guided PVB catheter, ultrasound-guided si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…Finally, five eligible RCTs were included in the meta-analysis. [14][15][16][17][18] The five eligible articles were carefully reviewed; their characteristics are provided in Table 1. The RCTs enrolled a total of 458 patients, and the results were published between 2015 and 2020.…”
Section: Literature Search and Selection And Quality Assessmentmentioning
confidence: 99%
“…Finally, five eligible RCTs were included in the meta-analysis. [14][15][16][17][18] The five eligible articles were carefully reviewed; their characteristics are provided in Table 1. The RCTs enrolled a total of 458 patients, and the results were published between 2015 and 2020.…”
Section: Literature Search and Selection And Quality Assessmentmentioning
confidence: 99%
“…TEA and para-vertebral block (PVB) have been recognized to be two major methods of postoperative analgesia not only for open thoracotomy but also for VATS (18,21,22). Although the incidence of minor side effects such as perioperative hypotension is less with PVB than with TEA, analgesic efficiencies, incidence of major side effects such as hematoma, and patients' outcomes are considered comparable between TEA and PVB (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hypotension and urinary retention were less frequent in the PVB group. In contrast, Yeap et al 12 reported lower pain scores and lower opioid consumption for TEA compared with PVB. Reconciling the study by Yeap et al 12 with the existing evidence presents a challenge because of some heterogeneity in PVB techniques and pain score assessment methods used.…”
mentioning
confidence: 90%
“…In this issue of the journal, Yeap et al 12 report on the findings of an interesting study comparing the effectiveness of TEA and PVB for postoperative pain control after VATS. With 3 interventional arms; 2 primary outcomes; and multiple secondary outcomes, including assessment of long-term chronic pain, this study undertook ambitious aims.…”
mentioning
confidence: 99%
See 1 more Smart Citation